An Assessment of Independent Sharī'a Panel (ISP) and Its Roles in Resolving Marital Conflicts in Osun State of Nigeria - Tijani Abdul-Lateef Aremu; Musa-Jeje Ibrahim Aladire; Alimi Lawal Sikiru (Al-Ahkam, 2022)
Every relationship, including marriage, is prone to conflict. There have been many solutions offered in dealing with this problem. The Independent Sharī’a Panel (ISP) in Osun State, Nigeria, is a panel that plays a role in resolving marital conflicts in Osun State. This article aims at describing the family conflict resolution program in Osun State. This article is a result of the study employing both quantitative and qualitative methods. The data gathered were from the field involving the interviews. This article reveals that marital conflict in Osun State is rampant and tends to increase yearly. This study also identified that the Independent Sharī’a Panel has served as a credible alternative mechanism, resulting in the resolution of many marital conflicts in this state. This research recommends that the Independent Sharīʿa Panel initiates a strong orientation program for young people on successful marriages, the consequences of marital discord, and how to resolve the issues.